2017
DOI: 10.1002/cncr.30838
|View full text |Cite
|
Sign up to set email alerts
|

The role of early magnetic resonance imaging in predicting survival on bevacizumab for recurrent glioblastoma: Results from a prospective clinical trial (CABARET)

Abstract: In this study, early progression on MRI appears to be a robust marker of a poor prognosis for patients on bevacizumab. Cancer 2017;123:3576-82. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Galla et al [33] showed that change in minimum ADC in the enhancing portion of the tumor after superselective intra-arterial bevacizumab therapy was associated with an increased risk of death (hazard ratio = 2.0, 95% confidence interval(CI) [1.04-3.79], p = .038), adjusting for age, tumor size, BV dose, and prior IV BV treatments. Field et al [34] concluded that early progression on MRI appears to be a robust marker of a poor prognosis for patients on bevacizumab. Mardor et al [35] described the use of diffusion weighted imaging (ADC and Radial diffusivity) from pretreatment MRI, and showed mild correlation with response, defined as relative change in the tumor size, but they did not report PFS6 or OS.…”
Section: Discussionmentioning
confidence: 99%
“…Galla et al [33] showed that change in minimum ADC in the enhancing portion of the tumor after superselective intra-arterial bevacizumab therapy was associated with an increased risk of death (hazard ratio = 2.0, 95% confidence interval(CI) [1.04-3.79], p = .038), adjusting for age, tumor size, BV dose, and prior IV BV treatments. Field et al [34] concluded that early progression on MRI appears to be a robust marker of a poor prognosis for patients on bevacizumab. Mardor et al [35] described the use of diffusion weighted imaging (ADC and Radial diffusivity) from pretreatment MRI, and showed mild correlation with response, defined as relative change in the tumor size, but they did not report PFS6 or OS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early response evaluation seems more reasonable. The analysis of MRI imaging data in the CABARET trial clearly showed that early MRI (after every treatment cycle) had prognostic value for overall survival (20). Likewise, in this study, we developed a surrogate imaging biomarker, ERI, to quantitatively measure the anti-edema effect of BEV as an indirect evaluation of the response of the patient to BEV therapy.…”
Section: Discussionmentioning
confidence: 92%
“…Early MRI progression was a strong independent predictor of mortality. 370 PMID: 28678383 T2WI and DCE-MRI Bevacizumab (+chemoradiation therapy) VEGF Glioblastoma 232 At weeks 6 and 12 of treatment, increases in baseline necrosis and de novo necrosis were strongly associated with worse OS and PFS. 371 PMID: 31076534 TME mapping Bevacizumab VEGF Glioblastoma 18 Higher percentage of neovascularization and active tumor in baseline indicated poor or no treatment response.…”
Section: Application Of Molecular Imaging In Targeted Therapymentioning
confidence: 99%